Evaluation and Development of Drinking Water Supply System (SPAM) IKK Perbaungan Serdang Bedagai Regency (Tunas Geografi, 2022)
The purpose of this study was to analyze the evaluation and development of SPAM IKK perbaungan, Serdang Bedagai Regency, North Sumatra. The method used in this research were preliminary study, data collection, data analysis, discussion, conclusions, and suggestions. Data collection was divided into primary data consisting of the existing condition of SPAM IKK Perbaungan, while secondary data consists of pipeline network, service data, and population data. At the same time, the data analysis was in the form of population projections, water demand projections, and evaluation of SPAM based on technical and institutional aspects. The questionnaire results showed that over 60% of the population who are not PDAM customers are interested in becoming customers and agreed to pay connection fees. SPAM IKK Perbaungan would serve four villages, namely Simpang Tiga Pekan,  Batang Terap, Citaman Jernih, and  Kota Galuh, with populations of 9,118, 3,352, 7,184, and 4,896, respectively. The implementation was divided into two stages, namely Phase I in 2022-2027, which served Simpang Tiga Pekan, Batang Terap, and Citaman Jernih with total water demand of 33.51 L/s, then Phase II in 2028-2032, which added to serve Kota Galuh with a total water demand of 42.41 L/s.Keywords: Evaluation, Development, Drinking Water Supply System